Effectiveness Of Rhythmic Gymnastics For The Development Of Gross Motor In Preschool Age Children - Awanis, Almas; Larasati, Nandang; Ariyanti, Lilik (FISIO MU: Physiotherapy Evidences, 2025)
Introduction: Gross motor skills are complex motor skills involving the large muscles of the arms, leg muscles, and most require coordination of all four limbs in children. Optimization is needed for gross motor development, one of which is by providing external stimulus, namely rhythmic gymnastics. Rhythmic gymnastics is a physical activity carried out with rhythmic accompaniment with complex movements and involving all body parts. The aim of this research is to determine the effectiveness of rhythmic gymnastics for the development of gross motor skills in preschool children. Methods: The type of research used in this research is quasi experimental, with a purposive technique sampling. The research sample was preschool aged children (5-6 years) with a total of 22 samples who were treated with rhythmic exercise 12 times for 4 weeks, with 3 times each week and 22 samples as the control group. The examination instrument in this study used TGMD-2 (Test of Gross Motor Development). Results: Based on statistical testers, it was found that rhythmic exercise was effective for the gross motor development of preschool children with p 0.00 < 0.05, which means that Ho was rejected and Ha was accepted. Conclusion: In this study was that whether rhythmic exercise was given or not, children still experienced an increase in gross motor development in both groups with a significant difference of 0.01 in the control group and 0.00 in the intervention group.